The dialogic negotiation of justice. Issue 2 (4th March 2021) - Shelley, Becky; Ooi, Can-Seng; Denny, Lisa
Abstract: The purpose of the paper is to reveal the complexities of negotiating justice. We present the case of workers' experiences during a long-running industrial dispute at Australia's first legal casino. First, we consider the concept of justice, drawing on discussions from tourism studies. This notion is considered in relation to an industrial dispute at the casino. Second, we use Bakhtin's dialogic imagination to explore the issues, primarily through the voices of the workers. The concepts of heteroglossia, polyphony and carnivalesque facilitate layering the voices and concerns of the workers. Formal and informal strategies to exert influence are present. Within the carnivalesque, there is order and disorder. Different parties present a cacophony of voices, asserting the just-ness of their position. We discuss how, as boundaries of social action are negotiated, the parties are effectively negotiating justice. Third, we suggest how, from our Bakhtinian perspective, justice is a social activity, doing justice is a social process, and achieving justice is hard. Finally, we share some broader suggestions and reflections on the complexities and contradictions.